Polythiophenes Comprising Conjugated Pendants for Polymer Solar Cells: A Review - Wang, Hsing-Ju (Materials (Basel), 2014)
Polythiophene (PT) is one of the widely used donor materials for solution-processable polymer solar cells (PSCs). Much progress in PT-based PSCs can be attributed to the design of novel PTs exhibiting intense and broad visible absorption with high charge carrier mobility to increase short-circuit current density (J(sc)), along with low-lying highest occupied molecular orbital (HOMO) levels to achieve large open circuit voltage (V(oc)) values. A promising strategy to tailor the photophysical properties and energy levels via covalently attaching electron donor and acceptor pendants on PTs backbone has attracted much attention recently. The geometry, electron-donating capacity, and composition of conjugated pendants are supposed to be the crucial factors in adjusting the conformation, energy levels, and photovoltaic performance of PTs. This review will go over the most recent approaches that enable researchers to obtain in-depth information in the development of PTs comprising conjugated pendants for PSCs.